2022
DOI: 10.3390/ph16010021
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Investigations of Allium scorodoprasum L. Flower Extracts

Abstract: This study was designed to investigate the impact of different extraction solvent systems on the chemical composition and biological activities of Allium scorodoprasum L. (Amaryllidaceae)—the medicinal plant that was traditionally used as a remedy in the medieval period in the Balkans. Targeted chemical analysis of nine different extracts was performed by UHPLC(−)HESI–QqQ-MS/MS. Antimicrobial and antibiofilm activities of the extracts were investigated on sixteen clinical isolates of bacteria, yeasts and derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…jajlae in our study, as determined by the GC-MS analysis, identified linoleic acid, palmitic acid, and octadecanoic acid 2,3-dihydroxypropyl ester as the major compounds in the ethanol extract. In contrast, Ðordevski et al [ 44 ] found flavonoids, such as rutin and kaempferol 3-O-glucoside, to be the most abundant compounds in the extracts of A. scorodoprasum L. flowers.…”
Section: Discussionmentioning
confidence: 94%
“…jajlae in our study, as determined by the GC-MS analysis, identified linoleic acid, palmitic acid, and octadecanoic acid 2,3-dihydroxypropyl ester as the major compounds in the ethanol extract. In contrast, Ðordevski et al [ 44 ] found flavonoids, such as rutin and kaempferol 3-O-glucoside, to be the most abundant compounds in the extracts of A. scorodoprasum L. flowers.…”
Section: Discussionmentioning
confidence: 94%
“…All the microoganisms were deposited at bacterial and fungal unit collection of the Mycological laboratory of the Institute for Biological Research “Siniša Stanković”, National Institute of the Republic of Serbia, University of Belgrade. Evaluated pathogenic microorganisms were clinical samples, isolated from the infected skin [ 49 ]. Antibacterial and anticandidal activities of TVH were evaluated using microdilution method in 96-well microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial and anticandidal activities of TVH were evaluated using microdilution method in 96-well microtiter plates. The minimum inhibitory concentrations (MIC) and minimal bactericidal/fungicidal concentrations (MBC/MFC) of extracts were determined as described previously [ 49 ]. Streptomycin and ketoconazole were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic effect of the extracts was determined using a spontaneously immortalized keratinocyte cell line (HaCaT, AddexBio T0020001) in the crystal violet assay, as previously described by Stojković et al [ 49 ] with some modifications. HaCaT cells were grown in high-glucose Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS, Gibco, Life Technologies Ltd., U.K.), 2 mM L-glutamine, and 1% antibiotic-antimycotic (Gibco, Life Technologies Corporation, Carlsbad, CA, USA) at 37 °C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as described by Đorđevski et al [ 49 ] with some modifications. HaCaT cells were grown until reaching 85% confluence.…”
Section: Methodsmentioning
confidence: 99%